2018
DOI: 10.2141/jpsa.0170188
|View full text |Cite
|
Sign up to set email alerts
|

Bitter Taste Sensitivity and the Expression of Bitter Taste Receptors at Different Growth Stages of Chicks

Abstract: Bitterness is one of the five basic tastes, and sensitivity to bitterness is important in that it enables animals to avoid harmful and toxic substances. In humans, taste sensitivity decreases with age, although the extent of loss varies depending on the taste quality. In chickens (Gallus gallus domesticus), baby chicks have been found to be more sensitive to salt and sour taste qualities than adults. In this study, therefore, we investigated the growth-associated changes in bitter taste sensitivity in chicks. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…It was reported earlier that in chickens, bitterness susceptibility is dependent on the age of the chicken, as bitter taste receptors were highly expressed in zero to one-week-old chicks and dependently decreased in aged chickens, and these behavioral responses were conserved since hatching to the maturing period [19,61]. However, insufficient research has been done to investigate growth-related taste perceptions and their subsequent effect on the animal’s growth [61,62]. Bitter molecules detected by the ggTas2R family of G-protein-coupled receptors (GPCRs) were involved in chickens perceiving potentially toxic compounds [63].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported earlier that in chickens, bitterness susceptibility is dependent on the age of the chicken, as bitter taste receptors were highly expressed in zero to one-week-old chicks and dependently decreased in aged chickens, and these behavioral responses were conserved since hatching to the maturing period [19,61]. However, insufficient research has been done to investigate growth-related taste perceptions and their subsequent effect on the animal’s growth [61,62]. Bitter molecules detected by the ggTas2R family of G-protein-coupled receptors (GPCRs) were involved in chickens perceiving potentially toxic compounds [63].…”
Section: Discussionmentioning
confidence: 99%
“…Recent behavioral experiments reveal that baby chicks have a greater aversion to salt and sour taste qualities than in adults [36]. A latest research on chickens shows that younger chicks are more sensitive to bitter compounds compared with older chicks [37]. Previously, it was reported that NaCl solutions of 85 mM and 100 mM are the preferred solutions for chickens, while chickens refused to accept NaCl solutions of 250 mM or higher concentration due to aversive taste [38].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we speculate that the age of chickens resulted in a reduction in their sensitivity to bitter compounds. Additionally, normal commercial feed does not contain strongly bitter substances [37]; therefore, the bitter taste experience of these chickens was not extensive under the experimental conditions of this study. Moreover, the long-term feed formulation and highly selective breeding of farm-raised chickens expose them to less toxic bitter substances that exist in nature.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of the differences in bitter taste sensitivity among growth stages using 0–1, 4–5, and 8–9 week-old chicks, behavioral tests showed that younger chicks are more sensitive to bitter compounds that activate cT2Rs ( Dey et al , 2018 ). The study also suggested that higher expression of the mRNA of one of the bitter taste receptors, cT2R1, in younger chicks may be involved in their high sensitivity to bitterness.…”
Section: Differences In Bitter Taste Sensitivity Among Growth Stages Chicken Strains and Poultry Speciesmentioning
confidence: 99%